Academic Senate Minutes 2004-03-18 - Academic Senate:::::::::
Chair's Report. Agenda amended and approved. Minutes of 2/5/04 and 2/19/04 approved. Faculty Emeritus eligible for Emeritus for Spring 2004 – Approved. Changes in the Psychology Major approved. From S&F: Amendment to Article III, Section 3.10 of By-Laws; Replacement of Lecturer Senators approved. From S&F: Amendment to Article III, Section 3 of By-Laws regarding election of Lecturer Senators approved. President's report. Budget Report from R. Armiñana, E. Ochoa, and L. Furukawa- Schlereth. Moment of silence for Tom Wagner. Resolution to Assess Faculty Confidence in SSU Academic Senate and Administration - Second Reading - tabled.